Geometriae Dedicata - Schlenker, Jean-Marc.; Parker, John R.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Geometriae Dedicata concentrates on geometry and its relationship to topology, group theory and the theory of dynamical systems. Geometriae Dedicata aims to be a vehicle for excellent publications in geometry and related areas. Features of the journal will include: A fast turn-around time for articles. Special issues centered on specific topics. All submitted papers should include some explanation of the context of the main results. Geometriae Dedicata was founded in 1972 on the initiative of Hans Freudenthal in Utrecht, the Netherlands, who viewed geometry as a method rather than as a field. The present Board of Editors tries to continue in this spirit. The steady growth of the journal since its foundation is witness to the validity of the founder's vision and to the success of the Editors' mission.
Keywords: Algebraic geometry; Convex geometry; Discrete geometry; Differential geometry; Hyperbolic geometry; Projective geometry; Topology; Convex and Discrete Geometry; Differential Geometry; Algebraic Geometry; Hyperbolic Geometry; Projective Geometry; Topology